PENGARUH KESADARAN WAJIB PAJAK DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DENGAN BUDAYA PAJAK SEBAGAI VARIABEL MODERASI (STUDI KASUS DESA BANGKALALOE, KECAMATAN BONTORAMBA, KABUPATEN JENEPONTO) - Ade Nurfatmawati Syam, Sri; Amir; Indrawahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of taxpayer awareness and tax knowledge on taxpayer compliance in paying Land and Building Tax (PBB), with tax culture as a moderating variable. The research was conducted in Bangkalaloe Village, Bontoramba District, Jeneponto Regency. A quantitative approach was employed with data collected from 350 respondents using purposive sampling. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results show that taxpayer awareness has a positive and significant effect on taxpayer compliance (β = 0.171; t = 2.105 > 1.96). Tax knowledge also has a positive and significant effect on taxpayer compliance (β = 0.830; t = 10.541 > 1.96). Furthermore, tax culture significantly moderates the relationship between taxpayer awareness and compliance (t = 116.059 > 1.96) as well as the relationship between tax knowledge and compliance (t = 48.821 > 1.96). These findings indicate that awareness, knowledge, and tax culture are key determinants of PBB compliance in rural communities. The government is encouraged to intensify tax socialization and strengthen tax culture through community-based approaches in order to optimize PBB revenue achievement.